Crosstalk between the Androgen Receptor and PPAR Gamma Signaling Pathways in the Prostate - Olokpa, Emuejevoke (PPAR Res, 2017)
Nuclear receptors are a superfamily of ligand-activated transcription factors that play critical roles in the regulation of normal biological processes and several disease states. Of the nuclear receptors expressed within the prostate, the androgen receptor (AR) promotes the differentiation of prostatic epithelial cells and stimulates production of enzymes needed for liquefaction of semen. Multiple forms of AR also promote the growth of both early and late stage prostate cancers. As a result, drugs that target the AR signaling pathway are routinely used to treat patients with advanced forms of prostate cancer. Data also suggest that a second member of the nuclear receptor superfamily, the peroxisome proliferator activated receptor gamma (PPARγ), is a tumor suppressor that regulates growth of normal prostate and prostate cancers. Recent studies indicate there is a bidirectional interaction between AR and PPARγ, with each receptor influencing the expression and/or activity of the other within prostatic tissues. In this review, we examine how AR and PPARγ each regulate the growth and development of normal prostatic epithelial cells and prostate cancers. We also discuss interactions between the AR and PPARγ signaling pathways and how those interactions may influence prostate biology.